A Study of Tyre, Cavity and Rim Coupling Resonance Induced Noise - Zamri, Mohamed; Wang, Xu; Ren, He; Liang, Xingyu; Shu, Hongli (Inderscience Enterprises Ltd., 2014)
The tyre cavity resonance induced noise and vibration currently have no effective mass production solutions. Al l proposed solutions are hard to service and difficult to maintain. Different analysis approaches are presented in this paper to verify computer simulati on models. Modal analysis results of the tyre cavity, tyre and rim structures were compared and a complex nature of tyre cavity acoustics is understood. Modified air cavities have been simulated. The research in this paper aims to find e ffective solutions for elimination of the coupled resonance mode by shifting the tyre cavity modal frequency